Willingness to use HIV pre-exposure prophylaxis among community-recruited, older people who inject drugs in Washington, DC. (1st July 2016) - Kuo, Irene; Olsen, Halli; Patrick, Rudy; Phillips, Gregory; Magnus, Manya; Opoku, Jenevieve; Rawls, Anthony; Peterson, James; Hamilton, Flora; Kharfen, Michael; Greenberg, Alan
Highlights: We studied HIV pre-exposure prophylaxis (PrEP) among older people who inject drugs. HIV PrEP knowledge and use was low in this population. Nearly half would be likely to use PrEP if it were available without cost. Younger, equipment-sharing PWID reported being very willing to use PrEP. Abstract: Introduction: Use of pre-exposure prophylaxis (PrEP) among people who inject drugs (PWID) has been shown to be effective in preventing HIV transmission. We examined correlates of the willingness to use PrEP among community-recruited older PWID in Washington, DC. Methods: PWID were recruited using respondent-driven sampling (RDS) and completed a behavioral interview for the National HIV Behavioral Surveillance system in 2012. Participants reported on willingness to use PrEP and how it might affect their drug use and sexual behaviors. We reported RDS-weighted proportions and multivariable correlates of being willing to use PrEP. Results: Among 304 participants, 69% were male, and the majority was aged ≥50 and black. Only 13.4% had ever heard of using anti-HIV medication to prevent HIV; none had ever used PrEP or knew anyone who used it in the past year. Forty-seven percent were very likely and 24% were somewhat likely to take PrEP if it were available without cost; 13% agreed they would not need to sterilize/clean needles or use condoms if taking PrEP. Correlates of being very likely to use PrEP included being younger (<50 years), sharing cookers, cotton or water in the past year, and believing they would no longer need to use clean needles. Conclusion: Nearly half of PWID reported being very willing to use PrEP if it were available without cost. Younger PWID and those at higher risk of sharing cookers, cotton or water were more willing to use PrEP, suggesting a focus on these groups to explore PrEP use among PWID.